Military Intelligence in Africa: Network Lens and Culture-Centric Focus : n/a - Putter, Dries; Salgado , Brock A.; John Melkon , John (Journal of Central and Eastern European African Studies, 2025)
Retraction Notice Article concerned: Putter, D., Salgado, B. A., & John Melkon, J. (2025). Military Intelligence in Africa: Network Lens and Culture-Centric Focus: n/a. Journal of Central and Eastern European African Studies, 5(3), 84–101. <a href="https://doi.org/10.12700/jceeas.2025.5.3.385" target="_blank" rel="noopener" data-saferedirecturl="https://www.google.com/url?q=https://doi.org/10.12700/jceeas.2025.5.3.385&source=gmail&ust=1763623866988000&usg=AOvVaw0BkrZeJtKABCrc4UJzav9M">https://doi.org/10.12700/jceeas.2025.5.3.385 Reason for retraction: Redundant publication Detailed information: On 16 November 2025, the author informed our editorial office that an article with similar content to the one published in JCEEAS had already been published in August 2025. Place of earlier publication: John Melkon, Brock A. Salgado & Dries Putter (03 Aug 2025): Networkcentric US military intelligence strategy for Africa's evolving geopolitical landscape, African Security Review, DOI: 10.1080/10246029.2025.2528706. In accordance with JCEEAS’s policies and the COPE Retraction Guidelines <a href="https://publicationethics.org/guidance/guideline/retraction-guidelines" target="_blank" rel="noopener" data-saferedirecturl="https://www.google.com/url?q=https://publicationethics.org/guidance/guideline/retraction-guidelines&source=gmail&ust=1763623866988000&usg=AOvVaw3n0rhac1P8MJtTYET4RbZ-">https://publicationethics.org/guidance/guideline/retraction-guidelines, an internal procedure was initiated. JCEEAS allows a maximum of 15% similarity with another study (see Call for Papers / Instructions for Authors). In this case, the similarity between the two articles substantially exceeded this threshold. Based on this, the editorial board concluded that the case constitutes redundant publication under the JCEEAS Plagiarism and Publication Malpractice Policy, and therefore decided to retract the article. In connection with this decision, we examined and documented the review and acceptance workflow: The author submitted the article to the JCEEAS system on 22 April 2025. JCEEAS completed the plagiarism check on 13 May 2025. At that time, the article in African Security Review had not yet been published, and therefore could not be detected during the plagiarism screening. The first version of the article in question appeared in African Security Review on 3 August 2025. JCEEAS published the article on 12 November 2025. Upon learning this, the author notified the editorial office on 16 November 2025 that the appearance of the two articles might constitute a case of redundant publication. This notice emphasises that, based on the available information, the author acted in good faith and reported the issue to the editorial office within a short time frame; therefore, no further ethical concerns arise in relation to this case. The retraction applies to both the online and offline versions of JCEEAS. In the online version, the retraction will be displayed by marking the affected article and publishing this Retraction Notice alongside it. Since the printed version of the issue was still in the printing phase during the procedure, the retracted article will not be included in the print edition.